Formulation of food grade Limosilactobacillus fermentum for antifungal properties isolated from home-made curd - Sucheta Mandal; Narayan Chandra Mandal (Scientific Reports, 2023)
Abstract Food spoilage has become a worldwide problem. Limosilactobacillus fermentum LAB212, isolated from home-made curd produces some potent antifungal compounds which can combat a wide range of spoilage and pathogenic fungi by disrupting their cell wall. Dual culture overlay assay and co-culture assay have confirmedly shown the potentiality of the strain. DOWEX50H + extraction and chemical characterization by high performance liquid chromatography show that lactic acid and acetic acid are playing the key roles in executing the antifungal activity. DPPH scavenging assay proves that the strain also exhibits a good antioxidant activity. After observing all the beneficial features and social need of the chemical preservative free food it is becoming highly prospective to exploite the strain commercially. In an experiment conducted for 180 days it was standardized that LAB212 supplemented with MRS and inulin is found most effective combination when challenged against the spoilage fungal species of Aspergillus flavus VBAH14, Penicillium rubens VBCA11, thus can be used as a very effective preservative agent. Using this strain as bio-preservative agent will also minimize the food borne diseases.